Genetic structure and phenotypic variation of Anopheles darlingi in northwest Colombia (2017)
This study evaluated the influence of environmental heterogeneity on Anopheles darlingi genetic and morphometric traits at a microgeographic level. Specimens of An. darlingi collected from multiple municipalities in the Colombian malaria endemic region Urabá-Bajo Cauca and Alto Sinú (UCS) were analyzed using 13 microsatellite loci. Spatial genetic structure, population variation and wing geometric morphometric analyses were performed. Microsatellite results showed low genetic differentiation and high gene flow among populations; four highly admixed subpopulations were detected with no particular association to the municipalities. Wing geometric morphometrics analysis showed a subtle but significant difference in wing shape for El Bagre vs. Mutatá populations, possibly influenced by geographical distance. Discrimination among populations in the morphospace showed a slight separation of the Tierralta population. There was no significant correlation between the genetic and geographic or genetic and environmental distances. We hypothesize that environmental heterogeneity in the UCS region does not reach a threshold to affect population structure of An. darlingi. Another possibility is that microsatellites are not sensitive enough to detect existing structure. It remains to be determined which local factors govern phenotypic variation among these populations and how, or whether these may affect mosquito biology and transmission capacity.